Properties of organosilicate low-k films with 1, 3- and 1, 3, 5-benzene bridges between Si atoms. (29th April 2020) - Liu, Chunhui; Lv, Chunguang; Kohler, Nicole; Wang, Xuesong; Lin, Hongxiao; He, Zhiwei; Wu, Yu-Hsuan; Leu, Jihperng; Wei, Shuhua; Zhang, Jing; Yan, Jiang; Palov, Alexander P.; et al.
Abstract: Organosilicate (OSG) low dielectric constant films containing different concentrations of 1, 3- and 1, 3, 5-benzene bridges between Si atoms are fabricated using 1, 3, 5-tribromobenzene via spin-on deposition and evaporation induced self-assembling. Chemical composition, pore structure, mechanical, dielectric and hydrophobic properties of as-prepared benzene bridged OSG thin films are studied using nuclear magnetic resonance, Fourier-transform infrared spectroscopy, ellipsometric porosimetry, nanoindentation, CV measurements and water contact angle. The precursors were synthesized by using two methods with the goal of understanding the effect of 1, 3, 5-benzene concentration on the films properties. It is shown that the films have very small pore size that does not change with porosity. No significant change in mechanical properties was observed at two different ratios of 1, 3- and 1, 3, 5-benzene bridged films.